IoT Enabled Stepper Motor Control for Industrial Automation Applications - R. Lakshmi Narayana; K. Nagabhushan Raju (Technological Innovation in Engineering Research Vol. 6, 2022)
By utilising the Internet of Things, product manufacturers may be able to automate operations and save money on manpower. By reducing production and distribution costs and enhancing transparency in product purchase and selling, it also eliminates waste and improves service delivery. The design and execution of an Internet of Things-based stepper motor control system are described in detail. Stepper motors have grown more appealing for use in robotics and computer numerical control machines, where they must execute high-precision positioning duties without the use of a feedback sensor, thanks to the advent of digital control systems. The goal of this project is to use a WiFi integrated microcontroller called NodeMcu to control actuators like stepper motors via the Internet of Things.